Prepectoral Implant-Based Breast Reconstruction and Postmastectomy Radiotherapy: Short-Term Outcomes. Issue 12 (December 2017) - Sigalove, Steven; Maxwell, G. Patrick; Sigalove, Noemi M.; Storm-Dickerson, Toni L.; Pope, Nicole; Rice, Jami; Gabriel, Allen
Abstract : Background: Prosthetic breast reconstruction in the setting of radiotherapy is associated with poor outcomes. Until recently, prosthetic breast reconstruction was predominantly performed by placing the prosthesis in a subpectoral space. Placement of the prosthesis in a prepectoral space is currently emerging as a simpler, alternative approach to subpectoral placement. The impact of postmastectomy radiotherapy (PMRT) on prepectoral reconstruction has not yet been specifically assessed. This study compared the outcomes of patients who underwent immediate, direct-to-implant, or 2-staged, prepectoral breast reconstruction followed by PMRT with those from patients who did not receive PMRT. Methods: Patients with well-perfused skin flaps and without contraindications, including uncontrolled diabetes-mellitus, previous irradiation, and current tobacco use, were offered the prepectoral approach. Following implant or expander placement, patients underwent planned or unplanned radiotherapy. Complications after each stage of reconstruction were recorded. Results: Thirty-three patients underwent 52 breast reconstructions via the prepectoral approach. Sixty-five percentage of the breasts were irradiated, including 21% after expander and 44% after implant placement. Patients were followed for a mean of 25.1 ± 6.4 months. Complication rate in irradiated breasts was 5.9% (1 incidence of seroma and 1 incidence of wound dehiscence followed by expander removal) and 0% in nonirradiated breasts. Capsular contracture rate was 0% in both irradiated and nonirradiated breasts. Conclusions: Immediate implant-based prepectoral breast reconstruction followed by PMRT appears to be well tolerated, with no excess risk of adverse outcomes, at least in the short term. Longer follow-up is needed to better understand the risk of PMRT in prepectorally reconstructed breasts.